Fabrication of sustainable insulation refractory: Utilization of different wastes - Hossain S.K.S.; Roy P.K. (My University, 2025)
The main objective of this study is to evaluate the use of different wastes as a raw material in the fabrication of insulation refractory. These wastes are fly ash, rice husk (RH), rice husk ash (RHA) and fired refractory grog. Various samples are prepared with different compositions based upon partial and fully replacement of clay by FA. Rice husk is used as an additive to produce the pores in the matrix. The specimens are prepared by semi dry process and sintering is performed at 800-1000 °C in air atmosphere. Numerous physical, mechanical and thermal characterizations like apparent porosity (AP), bulk density (BD), cold crushing strength (CCS), linear shrinkages, X-ray diffraction (XRD), scanning electron microscope (SEM) and thermal conductivity measurements of fired samples are done. The results show that the use of waste materials decreases the thermal conductivity and bulk density of the insulation refractory. Cold crushing strength of the 100 wt.% waste materials sample is around 15 MPa. This promising characteristic suggests that these wastes materials may lead to be used as a potential material for the preparation of insulation refractories. The use of waste materials may be economically attractive and technically feasible. © 2018 SECV.